Legal Analysis of the Death Penalty in Indonesia from the Perspective of National and International Law in Terms of Human Rights - Riyono, Dafid; Buaton, Tiarsen; Agus Suswantoro, Tri Agus Suswantoro (Institute for Law and Economics Studies, 2025)
This article discusses the regulation of capital punishment under international law as reviewed by the UN General Assembly Resolution on the Declaration of Human Rights of 1949 and its practice in several countries. The debate on the death penalty has led to the emergence of at least two major groups: those who oppose the death penalty and those who support it. Those who support the death penalty believe it is a necessary form of punishment to prevent and reduce crimes that are considered serious or extraordinary in society. The type of research used in this thesis is normative legal research. Normative legal research examines the law from an internal perspective, with the object of research being legal norms. The approaches used are the statutory approach, the conceptual approach, the case approach, and the comparative approach with several countries. The results of this study show that the regulation of the death penalty in international law shows a tendency towards abolition or very strict restrictions. UN General Assembly resolutions and instruments such as the UDHR and ICCPR provide a moral and normative basis for the rejection of the death penalty. However, its implementation is highly dependent on the socio-political conditions of each country. The future of the death penalty in international law will continue to be a tug-of-war between universal human rights principles and the reality of state sovereignty